2017
DOI: 10.1177/1363459316688517
|View full text |Cite
|
Sign up to set email alerts
|

Healthy habits are no fun: How Dutch youth negotiate discourses about food, fit, fat, and fun

Abstract: In this article, we use the notion of "biopedagogical practices" to explore how Dutch youth respond to health messages that focus on body weight. Previous studies suggest that such health messages encourage body dissatisfaction in youth. Few studies, however, focus on the local/cultural specificity of youth's responses to these biopedagogical practices. In this article, we address questions about the re-interpretation of and resistance to health messages that Dutch youth engage in and how these can be understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Participants shared an array of social media use habits they adopted over the course of their ED recovery journeys as they worked to create more constructive experiences of using Instagram for themselves that were supportive of their recoveries. In line with our theoretical lens of biopedagogies (Camacho-Miñano et al, 2019;van Amsterdam & Knoppers, 2018), participants' stories provide context for understanding complex processes of navigating and negotiating ED recoveries in relation to Instagram's visual landscape. Participants learned about and took up instructions about how to behave in their recoveries, while also, at times, rejecting or resisting these teachings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Participants shared an array of social media use habits they adopted over the course of their ED recovery journeys as they worked to create more constructive experiences of using Instagram for themselves that were supportive of their recoveries. In line with our theoretical lens of biopedagogies (Camacho-Miñano et al, 2019;van Amsterdam & Knoppers, 2018), participants' stories provide context for understanding complex processes of navigating and negotiating ED recoveries in relation to Instagram's visual landscape. Participants learned about and took up instructions about how to behave in their recoveries, while also, at times, rejecting or resisting these teachings.…”
Section: Discussionmentioning
confidence: 93%
“…Biopedagogies are instructions about how to live, typically rooted in ideals of health and beauty (Camacho-Miñano et al, 2019; van Amsterdam & Knoppers, 2018). Bio symbolizes a relationship to bodies (Harwood, 2012), and pedagogy relates to the ways in which people are taught to behave.…”
Section: Social Media Body Ideals and Eating Disorders: Theoretical O...mentioning
confidence: 99%
“…Incentives such as appearance and social popularity in specific social groups can motivate physical activity and dietary habits, resulting in perceptions of success (Wilhsson et al, 2017). In addition, engagement in health risk behaviours can be based on avoidance of social vulnerability rather than health risks (Randell et al, 2016;Van Amsterdam & Knoppers, 2018) as smoking and drinking alcohol has shown to strengthen the sense of belonging with friends (Randell et al, 2016). Koehn et al (2016) argue that adolescents may lack structure and perceived competence to sustain health behaviours in contexts where friends do not engage in these behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the most frequent categorization of methods included multiple methods ( n = 163), which varied from studies mixing interviews and focus groups (e.g. van Amsterdam and Knoppers, 2018) to a combination of collecting online data such as Twitter pages, blogs, and websites (Ashdown-Franks and Joseph, 2021), to a wider variety, such as Müller et al (2008) who used business plans, surveys, and in-depth interviews. However, on par with the emphasis on textual analysis, the dominant sole method 1 was collecting mass-media documents ( n = 141), such as newspaper texts (e.g.…”
Section: Analyzing and Summarizing The Findingsmentioning
confidence: 99%